Fundamentals of Supply Chain Management - Heri, Purwanto; Teguh, Wiharko; Edi, Andriansyah (INTI International University, 2025)
The author would like to express his gratitude to Allah SWT for His abundant blessings and grace, which have enabled this book entitled "Fundamentals of Supply Chain Management" to be compiled and completed successfully. This book covers a range of fundamental concepts to advanced strategies in supply chain management, including supply structure configuration, business relationships, technology integration, and customer orientation. This book can serve as a bridge of understanding for students, practitioners, and decision makers who want to manage supply chains more effectively and adaptively amid global challenges. This book still has many shortcomings in its compilation. The author would like to thank the various parties who have helped in the completion of this book. Hopefully, this book will serve as a clear and accessible reference and literature source.